Elevated plasma interleukin 34 levels correlate with disease severity-reflecting parameters of patients with haemorrhagic fever with renal syndrome. Issue 11 (2nd December 2019) - Tang, Kang; Zhang, Chunmei; Zhang, Yusi; Zhang, Yun; Du, Hong; Jin, Boquan; Ma, Ying
Abstract: Background: Haemorrhagic fever with renal syndrome (HFRS) is characterized by an uncontrolled cytokine storm that causes vascular leakage and kidney injury. The cytokine interleukin 34 (IL-34) enhances proliferation and differentiation of myeloid cells and secretion of pro-inflammatory cytokines, which is involved in the pathogenesis of some inflammatory and infectious diseases, including acute kidney injury. To date, however, the role of IL-34 in patients with HFRS is unclear. This study aims to determine the plasma IL-34 levels of HFRS patients and discuss the possible effects of IL-34 in the pathogenesis of HFRS. Methods: Plasma levels of IL-34 in 52 HFRS patients and 20 healthy controls were quantified using enzyme-linked immunosorbent assay. Results: Compared with healthy controls, the plasma IL-34 levels in HFRS patients were significantly elevated in acute phase [37.92 (0–215.45) pg/ml vs. 7.13 (0–19.44) pg/ml, p < .0001], and then decreased to the normal levels in convalescent phase. Importantly, IL-34 levels correlated positively with white blood cell counts and mononuclear cell counts ( r = 0.592, p < .0001 and r = 0.458, p < .0001, respectively), and correlated negatively with platelet counts and serum albumin levels ( r = −0.430, p < .0001 and r = −0.479, p = .0001, respectively). Conclusions: Plasma levels of IL-34 in HFRS patients were significantly elevated in acute phase and correlated with disease severity-reflecting parameters, which suggests a potential role of IL-34 in HFRS and should be future explored.